Intersection of race and socio-economic status on criminal judgments: high status reduces blame for Black juveniles but increases blame for White juveniles - Gilbert, Elizabeth A.; Guinn, Alexander D.; Reppucci, N. Dickon (Frontiers in Social Psychology, 2024)
IntroductionBoth Black juveniles and low-socioeconomic status (SES) juveniles are disproportionately represented in the U.S. legal system. Yet minimal experimental work has teased apart how a juvenile's race and SES interact when affecting judgments about guilt, blame, and punishment.MethodsTwo vignette experiments (N= 1074) varied a juvenile defendant's race (Black or White) and SES (low or high) in two types of crimes (stereotypically Black or stereotypically White).ResultsRace and SES interacted: across crime type, high-SES White juveniles were assigned more guilt and blame whereas high-SES Black juveniles were assigned less guilt and blame than their low-SES counterparts. Low-SES Black juveniles were also judged relatively harshly when their guilt was certain or when excluding participants who guessed the study was about race or SES. Moreover, stereotype-related judgments such as likelihood of recidivism and character mediated these effects.DiscussionThese surprising results highlight the need to investigate the intersection between race and SES. Potential explanations including aversive racism, social ecology, and changing stereotypes are considered.